The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.11604/pamj.2017.26.191.11476
|View full text |Cite
|
Sign up to set email alerts
|

Mesenteric cyst in infancy: presentation and management

Abstract: Mesenteric cysts are documented as a rare entity in pediatric population. They are considered as benign intra-abdominal tumors with an unknown etiology. Symptoms are not specific and knowledge of such condition is essential in order to establish a proper management. We report three pediatrics cases of mesenteric cysts managed between 2000 and 2009 in the pediatric surgery Department of Monastir College Hospital. We described the clinical, radiological and operative findings. Two males and a female were managed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 16 publications
0
10
0
2
Order By: Relevance
“…They are often located in the smallbowel mesentery and up to a third of patients have multiple cysts. However, they are most commonly singular, are multiloculated, and rarely contain chylous fluid ( 2 , 3 ). Chylous mesenteric cysts have an estimated incidence of 7.3% of all abdominal cysts ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are often located in the smallbowel mesentery and up to a third of patients have multiple cysts. However, they are most commonly singular, are multiloculated, and rarely contain chylous fluid ( 2 , 3 ). Chylous mesenteric cysts have an estimated incidence of 7.3% of all abdominal cysts ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mesenteric cyst (MC) is common in adults while in children and in infants is extremely rare (1)(2)(3). Clinical presentation may range from asymptomatic, a lump or pain in abdomen to intestinal obstruction or hemorrhage (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…The sonographic findings in our study demonstrated that a comprehensive analysis of mesenteric cysts via ultrasonography may provide an adequate differential diagnosis although due to the nature of the lesions, before surgical treatment, we advocate more precise radiological examinations. Computed tomography and magnetic resonance imaging can be helpful and essential in order to obtain better feature description of the mass (9). Additional information including the lesion origin, its relationships and its adhesion to visceral organs can be useful if laparoscopic surgery is being considered (10).…”
Section: Discussionmentioning
confidence: 99%
“…Uma vez que uma massa abdominal é suspeita, um exame ultrassonográfico deve ser realizado para uma avaliação radiológica inicial da lesão. Tomografia Computadorizada e Ressonância Magnética podem ser úteis a fim de obter uma resposta descritiva mais detalhada da massa, incluindo, por exemplo, informações como sua origem e relações anatômicas, bem como a sua adesão para os órgãos viscerais próximos, auxiliando no planejamento e na execução de um procedimento cirúrgico quando este for considerado (BELHASSEN et al, 2017). No caso supracitado, o exame tomográfico realizado descreveu múltiplas lesões císticas localizadas no mesentério, à esquerda, na altura do flanco e hipocôndrio, e considerou a possibilidade de natureza linfática.…”
Section: Para Se Prosseguir à Investigação Diagnóstica Foi Realizada Uma Ultrassonografiaunclassified